Integrated transcriptome and metabonomic analysis of key metabolic pathways in response to cadmium stress in novel buckwheat and cultivated species - Huo, Dongao; Hao, Ying; Zou, Juan; Qin, Lixia; Wang, Chuangyun; Du, Dengxiang (Frontiers in Plant Science, 2023)
Buckwheat (Fagopyrum tataricum) can be used both as medicine and food, which is also an important food crop in barren areas of land and has great economic value. Buckwheat is widely planted in Southwest China due to its barren resistance and other characteristics. It is difficult to avoid overlapping with the planting areas seriously polluted by cadmium (Cd) and other metals. Therefore, it is of great value to study the response of buckwheat to cadmium (Cd) stress and screen resistant materials to it. In this study, two critical periods of Cd stress treatment (day 7 and day 14) of cultivated buckwheat (Pinku-1, named K33) and perennial species (F.tatari-cymosum Q.F. Chen) (duoku, named DK19) were analyzed by using transcriptome and metabolomics methods. The results showed that Cd stress led to the change in reactive oxygen species (ROS), chlorophyll and photosynthetic respiratory system. Moreover, Cd response genes related to stress response, amino acid metabolism and ROS scavenging were enriched or activated in DK19. Compared with the cultivated buckwheat, the perennial species was more effective in enhancing Cd tolerance. Combination of transcriptomic and metabolomic analysis highlights the important role of galactose metabolism, lipid metabolism (glycerophosphatide metabolism and glycerophosphatide metabolism) and glutathione metabolism in response to Cd stress in buckwheat, which are significantly enriched at gene level and metabolic level in DK19. The results of the present study provide valuable information for a better understanding of the molecular mechanism underlying Cd tolerance of buckwheat, and also provide useful clues for the genetic improvement of drought tolerance in buckwheat.